The Analyzing Creative Thinking Skills of Junior High School Students in Solving Mathematical Problems with AI Assistance - Fauzi, Habibillah Achmad Putra; Siswono, Tatag Yuli Eko; Harini, Novita Vindri (MATHEdunesa, 2025)
This study analyzed the creative thinking ability of junior high school students in solving mathematics problems with the help of Artificial Intelligence (AI). The research employed a qualitative case study approach with three ninth-grade students of varying mathematical abilities (high, medium, and low). Data were collected through tests, observations, and interviews, then analyzed based on creative thinking indicators: fluency, flexibility, originality, and elaboration. The results showed that students' creative thinking skills were in line with their level of mathematical ability, where students with high mathematical ability were able to solve problems using unique approaches and detailed steps. However, there were minor errors in the conclusions. Students with moderate math abilities can use two different strategies, but they are still affected by AI solutions. Students with low math abilities tend to rely on AI-generated answers without modification. This study concludes that students' creative thinking ability is influenced by their conceptual understanding and how they utilize AI. Teachers need to guide students to use AI as an exploration tool, not just a source of answers.